Two SUMO Proteases SUMO PROTEASE RELATED TO FERTILITY1 and 2 Are Required for Fertility in Arabidopsis. Issue 4 (24th October 2017) - Liu, Linpo; Jiang, Ying; Zhang, Xiaomei; Wang, Xu; Wang, Yanbing; Han, Yuzhen; Coupland, George; Jin, Jing Bo; Searle, Iain; Fu, Yong-Fu; Chen, Fulu
Abstract : SUMO proteases regulate plant fertility through multiple pathways. Abstract: In plants, the posttranslational modification small ubiquitin-like modifier (SUMO) is involved in regulating several important developmental and cellular processes, including flowering time control and responses to biotic and abiotic stresses. Here, we report two proteases, SUMO PROTEASE RELATED TO FERTILITY1 (SPF1) and SPF2, that regulate male and female gamete and embryo development and remove SUMO from proteins in vitro and in vivo. spf1 mutants exhibit abnormal floral structures and embryo development, while spf2 mutants exhibit largely a wild-type phenotype. However, spf1 spf2 double mutants exhibit severe abnormalities in microgametogenesis, megagametogenesis, and embryo development, suggesting that the two genes are functionally redundant. Mutation of SPF1 and SPF2 genes also results in misexpression of generative- and embryo-specific genes. In vitro, SPF1 and SPF2 process SUMO1 precursors into a mature form, and as expected in vivo, spf1 and spf2 mutants accumulate SUMO conjugates. Using a yeast two-hybrid screen, we identified EMBRYO SAC DEVELOPMENT ARREST9 (EDA9) as an SPF1-interacting protein. In vivo, we demonstrate that EDA9 is sumolyated and that, in spf1 mutants, EDA9-SUMO conjugates increase in abundance, demonstrating that EDA9 is a substrate of SPF1. Together, our results demonstrate that SPF1 and SPF2 are two SUMO proteases important for plant development in Arabidopsis ( Arabidopsis thaliana ).